2018
DOI: 10.1016/j.ijid.2018.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and etiology of bacterial meningitis in Chinese children >28 days of age, January 2014–December 2016: A multicenter retrospective study

Abstract: The occurrence of BM peaked in the first year of life, while S. pneumoniae was the predominant pathogen in children >3months of old. The antibiotic resistance of S. pneumoniae was a concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 21 publications
11
28
0
Order By: Relevance
“…Bacterial meningitis remains a serious threat to children's health worldwide despite signi cant progress in the diagnosis and treatment of the disease. Of the 1142 patients in our study, 65.9% (753) were less than 1 year old, and over two-fths (513, 44.9%) were younger than 3 months, which was consistent with some previous studies [13,18]. These results indicated that most BM cases occurred in infants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Bacterial meningitis remains a serious threat to children's health worldwide despite signi cant progress in the diagnosis and treatment of the disease. Of the 1142 patients in our study, 65.9% (753) were less than 1 year old, and over two-fths (513, 44.9%) were younger than 3 months, which was consistent with some previous studies [13,18]. These results indicated that most BM cases occurred in infants.…”
Section: Discussionsupporting
confidence: 91%
“…One study from the southwest provinces of China reported that approximately 46% of PBM cases were caused by Escherichia coli (E. coli) and S. pneumoniae from 2012 to 2015 [11]. The etiology of PBM varies greatly based on several factors, including geographical location, time, and age of the patients [8,[11][12][13]. In addition to their isolation rates, their AMR patterns vary substantially [14].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand more than half of E. coli (60%) was resistant to penicillin G in this study, which in line with study conducted in china which showed more than half of E. coli showed resistance to penicillin (42). In the present study E. coli showed the highest resistance to penicillin G (60%) followed by H. influenzae b (50%) and S. pneumoniae (38.5%).…”
Section: Discussionsupporting
confidence: 89%
“…In two other hospitals in South China, GBS was the predominant pathogen associated with NS at 5.2–31.3%, which were higher values than those in middle China during the same period 7,9,23. Moreover, GBS (46.5%) was recently reported as the leading organism, followed by E. coli (23.3%) and S. aureus (7.0%), in infants <3 months old in a multicenter study on Chinese children diagnosed with bacterial meningitis between 28 days and 6 years of age, excluding neonates 24. GBS was the most common pathogen in both early-onset and late-onset bacterial meningitis.…”
Section: Discussionmentioning
confidence: 78%